Furman v. Georgia : cruel and unusual punishment - Roensch, Greg. (New York : Chelsea House, 2007)
Provides an account of the Supreme Court case of Furman v Georgia in which the Court overturned the imposition of the death penalty for convicted murderer William Henry Furman after hearing arguments that the death sentence constituted cruel and unusual punishment and was in violation of the Eighth and Fourteenth amendments.
A brief history of the death penalty -- Background of the Furman case -- Furman goes to the Supreme Court -- The historic opinion -- After the decision -- The death penalty today.
Includes bibliographical references (p. 105-106) and index.
8.7
5-8
Keywords: Furman, William Henry; Capital punishment